2021
DOI: 10.1007/s11661-021-06204-w
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic Simulation on the Mechanical Properties of Diffusion Bonded Zr-Cu Metallic Glasses with Oxidized Interfaces

Abstract: A novel welding technique of diffusion bonding for Zr-Cu metallic glass with pre-oxidized surfaces is proposed in this study, which is systematically investigated by molecular dynamics (MD) simulation. Compared with the conventional welding technique, the diffusion bonding process can be well implemented below the crystallization temperature of metallic glass. The obtained structure possesses glass-glass interfaces (GGIs) similar with those in nano-glasses.As revealed by MD simulation, the diffusion bonded met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…For instance, Adibi et al [ 40 , 41 ] demonstrated the capability of shear bands in NGs to be uniformly distributed within the GGI regions, which was further explained by Wang et al [ 42 ], who demonstrated that the GGIs would promote the plastic deformations in NGs. In other words, the GGIs could significantly influence the shear banding in NGs [ 43 , 44 , 45 , 46 , 47 , 48 ], although a viable strategy for controlling shear banding through alternating the glass phase of GGIs is yet not available, which is critical to further improving the ductility of NGs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Adibi et al [ 40 , 41 ] demonstrated the capability of shear bands in NGs to be uniformly distributed within the GGI regions, which was further explained by Wang et al [ 42 ], who demonstrated that the GGIs would promote the plastic deformations in NGs. In other words, the GGIs could significantly influence the shear banding in NGs [ 43 , 44 , 45 , 46 , 47 , 48 ], although a viable strategy for controlling shear banding through alternating the glass phase of GGIs is yet not available, which is critical to further improving the ductility of NGs.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic glasses (MG) have attracted many attentions owing to the particular performances in structures and properties different from the crystalline phases [1][2][3][4][5][6][7]. Zr-based MG are widely used in vehicle parts, sports equipment and so on, attributing to the superb mechanical properties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%